O GÊNERO TILLANDSIA L. (BROMELIACEAE-TILLANDSIOIDEAE) NO ESTADO DO PARANÁ, BRASIL. - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
Tillandsia L. is the largest genus of the subfamily Tillandsioideae (Bromeliaceae) with ca. 557 species. It is distributed from the southern U. S. A to central Argentina and Chile. Traditionally the genus has been divided into seven subgenera: Tillandsia subg. Allardtia (A. Dietrich) Baker, Tillandsia subg. Anoplophytum (Beer) Baker, Tillandsia subg. Phytarrhiza (Vis.) Baker, Tillandsia subg. Diaphoranthema (Beer) Baker, Tillandsia subg. Tillandsia L., Tillandsia subg. Pseudalcantarea Mez and Tillandsia subg. Pseudo-Catopsis Baker. The taxonomic study of the species Tillandsia in the Paraná state was presented. Were found 17 species in 4 subgenera:Tillandsia subg. Diaphoranthema -Tillandsia loliacea Mart. ex Schult. & Schult.f., Tillandsia recurvata (L.) L, Tillandsia tricholepis Baker and Tillandsia usneoides (L.) L.; Tillandsia subg. Anoplophytum -Tillandsia didisticha (E. Morren) Baker, Tillandsia gardneri Lindley, Tillandsia geminiflora Brong., Tillandsia lineares Vell., Tillandsia lorentziana Griseb.; Tillandsia pohliana Mez, Tillandsia recurvifolia Hooker, Tillandsia stricta Solander, Tillandsia tenuifolia L.; Tillandsia subg. Phytarrhiza - Tillandsia crocata (E. Morren) Baker, Tillandsia streptocarpa Baker; Tillandsia mallemontii Glazou ex Mez e Tillandsia subg. Tillandsia -Tillandsia polystachia (L.) L.. Identification Keys, as well as descriptions, illustrations, comments and distribuition patterns are presented. The results show that the Paraná has a high species richness when compared to neighboring states. Besides the taxonomic study, there were some evolutionary adaptations of species, fitting them in ecophysiological types proposed in the literature. Only T. polystachia presents wide rosette forming tank. The remaining species are characterized by the absence of the tank, the presence or absence of non-root in adulthood and four species were found to be minimized.
Keywords: Bromeliaceae; Tillandsia; taxonomia; adaptações evolutivas; Paraná; Bromeliaceae; Tillandsia; taxonomy; evolutionary adaptations; Paraná; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR